Optical conformable electromotive with spherical antiferromagnetic flux intensity - Körpınar, Talat; Körpınar, Zeliha (Springer, 2023)
In this manuscript, we define spacetime conformable optical electromotive of conformable Ss-fibers with spherical conformable frame. Thus, we demonstrate important optical conditions with spherical antiferromagnetic conformable optical magnetic flux intensity. Moreover, we obtain conformable spherical optical antiferromagnetic electromotive xi(S)(nu)(gamma(S)), xi(S)(nu)(e), xi(S)(nu)(s) forces (A)epsilon(nu)(phi(gamma S)), (A)epsilon(nu)(phi(e)), (A)epsilon(nu)(phi(s)). Finally, electromagnetic conformable optical spherical fibers are determined by electromagnetic fluctuations of spherical conformable spherical magnetic flux intensities in the uniform electromagnetic surface of conformable Ss-fibers.
Keywords: Spherical conformable frame; Spherical antiferromagnetic electromotive; Antiferromagnetic spin; Conformable flux intensity